EVALUASI KINERJA PORTOFOLIO SAHAM SEKTOR CONSUMER GOODS DI PASAR MODAL INDONESIA - , Anestia Amelia ([Yogyakarta] : Universitas Gadjah Mada, 2013)
During the year 2010-2012 the Stock Composite Index (IHSG) showed positive movements. Entering November 2012, the index started to decline. This was because the market players had started to pay attention on the global economy issues. Uncertainty sentiment on the global condition still had an influence on the stock trading in Indonesia. Therefore, stock investment allocation would be better in the stocks with domestic orientation such as banking sector stock, infrastructure stock, consumer goods stock, and retail stock. The consumer goods sector was able to survive the crisis and provide good prospects to the investors particularly for long term investment. The consumer goods sector stocks includes the defensive sector and is an economy sector that is related to the wellbeings of many